Genus Allium: The Potential Nutritive and Therapeutic Source - Ghazala H. Rizwani; Huma Shareef (Journal of Pharmacy and Nutrition Sciences, 2011)
The two Allium species, Onion (Allium cepa L.) and garlic (Allium sativum L.) are the most edible and oldest cultivated plants. These two species have not only beneficial effects against disease also they have nutritive potential. They are very rich sources of several phytonutrients, electrolytes, carbohydrates, minerals, and vitamins and documented to have a significant identical pharmacological characteristic including hypocholestremic, hypotensive, hypoglycecmic, antithrombotic and anti allergic as well as wide range of biological activities such as anti-inflammatory, antimicrobial, antifungal and antioxidants. This review article will scan the nature with understanding, thinking, realizing and utilization of these two herbs for their therapeutic source in adding together their nutritive potential. In this review we focused on the nutritional attributes along with their curative potential of species of Allium genus (onion and garlic) belonging to the family Alliaceae.